Convective drying of bitter yam slices (Dioscorea bulbifera): Mass transfer dynamics, color kinetics, and understanding the microscopic microstructure through MATLAB image processing - Monalisa Sahoo; Vivek Kumar; S.N. Naik (Food Physics, 2024)
The objective of this research endeavor was to enhance the quality and storability of Dioscorea bulbifera through the investigation of the effects of pre-treatment (soaking) and different dehydration temperatures (50, 60, and 70°C) on its mass transfer, color kinetics, texture, microstructure, and rehydration properties. Ten drying and four-color kinetics models were employed to describe drying behavior and color changes. The drying process demonstrated a falling rate, with reduced drying time (from 960 to 540 min) as the convective temperature increased from 50 to 70°C. Moisture diffusivity increased with increasing hot air temperatures (4.15 ×10–10 – 1.03 ×10–9 m2/s), and the activation energy was determined as 41.82 kJ/mol. Slices dried at 70 °C exhibited higher color change than those dried at 50°C. The modified color model fitted the best color parameters, followed by the fraction model. Slices dried at 60°C showed lower hardness (34.73 N) and higher porosity (27.03 %) as compared with 50°C (49.33 N and 19.82 %) and 70°C (40.16 N and 21.90 %) temperature. Microstructure, moisture diffusion, and texture were closely linked to temperature and moisture content. Boiling and potassium metabisulfite significantly affected drying rate and texture of yam slices . MATLAB analysis provided detailed pore information for each hot air-dried sample, correlating with texture characteristics. This research offers substantial industrial significance by providing methods to enhance dried yam products' quality, shelf-life enhancement, and further exploration of starch extraction and recovery of valuable bioactive compounds.